2022
DOI: 10.30541/v44i4iipp.975-1001
|View full text |Cite
|
Sign up to set email alerts
|

Interest Rate Pass-through in Pakistan: Evidence from Transfer Function Approach

Abstract: The transmission of monetary policy through the interest rate mechanism has been thoroughly discussed in economic literature for quite some time. The traditional view is that, the change in real interest rate influences the cost of capital. The change in cost of capital affects the magnitude of investment and consumption and therefore the level of, real income and prices [Mishkin (1995)].1 Operationally the State bank of Pakistan, influences the yield on treasury bills … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
16
0
2

Year Published

2022
2022
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 4 publications
1
16
0
2
Order By: Relevance
“…Penelitian-penelitian yang relatif lebih baru dengan data yang lebih panjang seperti De Bondt (2005) yang menguji interest rate pass-through di negara-negara Euro, Chong et al (2006) untuk data Singapura, Horváth et al (2004) di Hungaria, dan Qayyum et al (2005) di Pakistan semuanya juga menunjukkan adanya friksi pada transmisi kebijakan moneter yang dilancarkan oleh otoritas moneter masing-masing negara tersebut sehingga reaksi perubahan suku bunga perbankan terhadap kebijakan moneter terjadi secara relatif lambat. Setiap negara tersebut memiliki faktor penentu interest rate pass-through yang spesifik karena kondisi perbankan, industri keuangan non-bank, pasar modal, dan sistem keuangan yang berbeda-beda.…”
unclassified
See 1 more Smart Citation
“…Penelitian-penelitian yang relatif lebih baru dengan data yang lebih panjang seperti De Bondt (2005) yang menguji interest rate pass-through di negara-negara Euro, Chong et al (2006) untuk data Singapura, Horváth et al (2004) di Hungaria, dan Qayyum et al (2005) di Pakistan semuanya juga menunjukkan adanya friksi pada transmisi kebijakan moneter yang dilancarkan oleh otoritas moneter masing-masing negara tersebut sehingga reaksi perubahan suku bunga perbankan terhadap kebijakan moneter terjadi secara relatif lambat. Setiap negara tersebut memiliki faktor penentu interest rate pass-through yang spesifik karena kondisi perbankan, industri keuangan non-bank, pasar modal, dan sistem keuangan yang berbeda-beda.…”
unclassified
“…Peneltian Qayyum et al (2005) dengan data negara Pakistan menemukan pass-through dari policy rate (T-Bills rate) kepada call money rate terjadi sempurna dalam jangka waktu sebulan, sementara pass-through kepada bunga deposito dan kredit terjadi jauh lebih lambat. Ringkasan hasil penelitian interest rate pass-through di beberapa negara dapat diihat pada Tabel 1.…”
unclassified
“…Given the role of country specific financial sector developments in determining the speed and degree of interest rate pass-through, the issue has been the subject of at least three studies in our knowledge. Qayyum et al (2005) was the first to take up this issue and estimated a transfer function by using monthly data on key interest rates from March 1991 to December 2004. Their results indicated that pass-through from T-bill rate to call money rate is almost one-to-one and completed during a month.…”
Section: Studies On Pakistanmentioning
confidence: 99%
“…The current monetary policy stance is silent on the issues of lags and the passthrough effect of the policy rate to inflation. There is evidence based on empirical analysis that the interest rate influences the rate of inflation with a lag of 12 to 18 months, and the magnitude of this impact is very small Qayyum, Khan, & Khawaja, 2007). Indeed, some studies show that the relationship between the interest rate and rate of inflation is positive (Khan, 2007).…”
Section: Ineffectiveness Of Monetary Policymentioning
confidence: 99%